2012
DOI: 10.1002/ppul.22506
|View full text |Cite
|
Sign up to set email alerts
|

Restrictive pulmonary dysfunction and its predictors in young patients with β‐thalassaemia major

Abstract: Our study shows that pulmonary impairment is shown in a great proportion even among asymptomatic young thalassaemic patients, thus, regular screening of pulmonary function should be adopted in the routine clinical follow up of these patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

7
24
0
6

Year Published

2013
2013
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(37 citation statements)
references
References 28 publications
7
24
0
6
Order By: Relevance
“…This is similar to other published studies done by Rahim et al 4 and Bourli et al 6 where restrictive abnormalities were most frequently reported. Studies done by Kanj et al 4 and Amin et al 7 showed both Obstructive and Restrictive pattern of Respiratory dysfunction.…”
Section: Discussionsupporting
confidence: 82%
“…This is similar to other published studies done by Rahim et al 4 and Bourli et al 6 where restrictive abnormalities were most frequently reported. Studies done by Kanj et al 4 and Amin et al 7 showed both Obstructive and Restrictive pattern of Respiratory dysfunction.…”
Section: Discussionsupporting
confidence: 82%
“…However, only two reports have described this fibrosis through recognition of areas of air-trapping on imaging techniques (high-resolution computed tomography) and showed the presence of iron-laden macrophages in bronchoalveolar lavage suggestive of lymphocyte alveolitis and interstitial fibrosis (Filosa et al, 2000;Piatti et al, 2006). Various studies have unsuccessfully searched for an association between pulmonary alterations and iron accumulation (estimated through serum ferritin levels or liver iron overload evaluated through T2* MRI): a relationship with serum ferritin levels has been described in a few cases (Kanj et al, 2000), but this association was not confirmed by other authors (Filosa et al, 2001;Abu-Ekteish et al, 2007;Bourli et al, 2012). Various studies have unsuccessfully searched for an association between pulmonary alterations and iron accumulation (estimated through serum ferritin levels or liver iron overload evaluated through T2* MRI): a relationship with serum ferritin levels has been described in a few cases (Kanj et al, 2000), but this association was not confirmed by other authors (Filosa et al, 2001;Abu-Ekteish et al, 2007;Bourli et al, 2012).…”
Section: Discussionmentioning
confidence: 99%
“…Serum ferritin düzeylerinin restriktif patern saptanan grupta, normal SFT olan gruba göre daha yüksek düzeyde olduğu gösterilmiştir 82 . Srittippayawan ve arkadaşları tarafından yapılan bir çalışmada 9-15 yaş arası, ayda bir kez transfüze edilen, şelasyon tedavisi almayan 21 talasemi majör tanılı hasta değerlendirilmiştir.…”
Section: Solunum Sistemi Bulgularıunclassified
“…Fung ve arkadaşlarının bir çalışmasında ise, hepatosplenomegalinin restriktif solunum fonksiyon bozukluğuyla ilişkili olmadığı gösterilmiştir 77 . Başka bir çalışmada ise, splenektomi yapılan ve yapılmayan hastalar ile restriktif SFT bozukluğu arasında anlamlı ilişki saptanmamıştır 82 .…”
Section: Solunum Sistemi Bulgularıunclassified